Analisis Bahan Ajar Akidah Akhlak Kelas V MI Terbitan Kemenag RI Dalam Perspektif Kurikulum Berbasis Cinta - Maslani, Maslani; Maulana, Ahmad Nanda; Al-Fathoni, Bilal Zakawali; Nurhakim, Dede Arif Rahman; Nurlela, Risma (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the fifth-grade Islamic Creed and Morals (Akidah Akhlak) teaching materials published by the Ministry of Religious Affairs of the Republic of Indonesia through the lens of the Love-Based Curriculum. This curriculum emphasizes compassion, empathy, and spirituality as the foundation of education. Utilizing a literature review method, this article examines the extent to which values of love towards God, fellow humans, the environment, and oneself are integrated into the content of the teaching materials. The analysis reveals that although the material aligns with the national curriculum standards, its approach remains primarily cognitive and normative. The affective, reflective, and spiritual aspects that are central to the Love-Based Curriculum have not been fully developed, particularly in stimulating students' emotional experiences and nurturing a deep, heartfelt connection. Therefore, it is essential to strengthen the elements of compassion and love-centered pedagogy so that the teaching of Islamic Creed and Morals not only produces intellectually capable students but also morally upright individuals filled with love in their everyday lives.